Characterization of a preferred site on human chromosome 19q for integration of adeno-associated virus DNA by non-homologous recombination. - Kotin, R M (1992)
The human parvovirus, adeno-associated virus (AAV), has been shown to integrate preferentially into human chromosome 19 q13.3-qter. The human target sequence for AAV integration (AAVS1) was cloned and sequenced. By analysis of the proviral junctions it was determined that integration of the AAV DNA occurred via a non-homologous recombination pathway although there were either four or five identical nucleotides at the junctions. Integration was a multistep, concerted process that resulted in cellular sequence rearrangements. The sequence of the integration locus was analyzed for possible recombination signals. Direct repeats at a much greater than random occurrence were found distributed non-uniformly throughout the AAVS1 sequence. A CpG island containing transcription factor binding site elements is suggestive of a TATA-less promoter. Evidence for transcriptional activity was provided by PCR amplification of reverse transcribed RNA.